Emission of Methane From Enteric Fermentation: National Contribution and Factors Affecting it in Livestock - Haryanto, Budi; Thalib, A (Indonesian Bulletin of Animal and Veterinary Sciences, 2009)
Changing in atmosphere condition is affected by the quantity of gases produced from all activities on the earth. Gases that have effects  on  global  warming  are  CO2,  N2O,  H2O,  and  CH4  (methane).  Among  other  sources  of  methane  are  enteric fermentation of organic material from ruminants and feces decomposition. Methane production from ruminants is affected by several factors such as breed/type of animal, feed quality, environmental temperature and physiological status of the animal. Energy as methane in ruminants may reach 2 to 15% of the total energy consumption. To reduce the emission of methane from ruminants, it is necessary to apply a strategic feeding system for more efficient utilization of feed.   Key words: Methane, global warming, ruminants, rumen fermentation